The man who hated women : sex, censorship, and civil liberties in the gilded age - Sohn, Amy, 1973- (Farrar, Straus and Giroux, 2021)
"A narrative history about Anthony Comstock, US Postal Inspector and vice hunter, and the remarkable women who opposed him"--